Society, ethics, and technology - Winston, Morton E. (Thomson/Wadsworth, 2006)
How do technology innovations create new ethical problems for our society? SOCIETY, ETHICS, AND TECHNOLOGY presents historical, social, and philosophical perspectives on technological change and its social consequences. Providing a strong foundation in both theoretical and applied ethical matters, this anthology encourages you to consider the social effects of the technology that surrounds you in your everyday life